Replacement of extension? Changes in the Economy of the Selk'Nam Hunter-Gatherer groups of central Isla Grande de Tierra del Fuego in the XIXth Century - Parmigiani, Vanesa Esther; de Angelis, Hernan Horacio; Mansur, Maria Estela
Tierra del Fuego has a large documentary register concerning the original huntergatherer societies as well as the arrival of European sailors, since the sixteenth century, and the establishment of settlers since mid-nineteenth century. The archaeological record lets verify changes and continuities in aboriginal way of life during the forced contact period, until the disappearance of Indian societies. In this paper we discuss two aspects that we could analyze from the archaeological record of Ewan site: utilization of new raw materials and new faunal resources. Fil: Parmigiani, Vanesa Esther. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: de Angelis, Hernan Horacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Mansur, Maria Estela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina